2021
DOI: 10.1371/journal.pone.0260366
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of a reduced model of thrombosis under flow: Roles of Factor IX, Factor XI, and γ‘-Fibrin

Abstract: A highly reduced extrinsic pathway coagulation model (8 ODEs) under flow considered a thin 15-micron platelet layer where transport limitations were largely negligible (except for fibrinogen) and where cofactors (FVIIa, FV, FVIII) were not rate-limiting. By including thrombin feedback activation of FXI and the antithrombin-I activities of fibrin, the model accurately simulated measured fibrin formation and thrombin fluxes. Using this reduced model, we conducted 10,000 Monte Carlo (MC) simulations for ±50% vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The Monte Carlo approach, where about 10 4 À 10 5 simulations are performed with randomly selected input values, was followed by a few groups in the past. 17,18,[20][21][22] This methodology is accurate but time consuming and hardly tractable for complex models. Several parametric studies were also performed, where the outcome of the model is analysed for different deficiencies in coagulation factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Monte Carlo approach, where about 10 4 À 10 5 simulations are performed with randomly selected input values, was followed by a few groups in the past. 17,18,[20][21][22] This methodology is accurate but time consuming and hardly tractable for complex models. Several parametric studies were also performed, where the outcome of the model is analysed for different deficiencies in coagulation factors.…”
Section: Introductionmentioning
confidence: 99%
“…Making the models useful in the current efforts towards a better understanding of coagulation requires knowing how thrombin production depends on the uncertain inputs. The Monte Carlo approach, where about 104105 simulations are performed with randomly selected input values, was followed by a few groups in the past 17,18,20–22 . This methodology is accurate but time consuming and hardly tractable for complex models.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between thrombin and γ ′ fibrinogen may also provide possible avenues to develop targeted, thrombin-exosite peptides that exploit thrombin allostery [ 15 , 19 , 20 ]. Low levels of γ ′ fibrin(ogen) are associated with increased fibrin generation and increased thrombin generation [ 21 ]. Additionally, it has been suggested that fibrin-trapped thrombin, or the disruption thereof, could play a role in the observed fibrinolytic breakdown as a result of COVID-19 infection that leads to unintended bleeding and clotting.…”
Section: Introductionmentioning
confidence: 99%